Comparative Genomics of Mortierellaceae Provides Insights into Lipid Metabolism: Two Novel Types of Fatty Acid Synthase - Heng Zhao; Yong Nie; Yang Jiang; Shi Wang; Tian-Yu Zhang; Xiao-Yong Liu (Journal of Fungi, 2022)
Fungal species in the family Mortierellaceae are important for their remarkable capability to synthesize large amounts of polyunsaturated fatty acids, especially arachidonic acid (ARA). Although many genomes have been published, the quality of these data is not satisfactory, resulting in an incomplete understanding of the lipid pathway in Mortierellaceae. We provide herein two novel and high-quality genomes with 55.32% of syntenic gene pairs for Mortierella alpina CGMCC 20262 and M. schmuckeri CGMCC 20261, spanning 28 scaffolds of 40.22 Mb and 25 scaffolds of 49.24 Mb, respectively. The relative smaller genome for the former is due to fewer protein-coding gene models (11,761 vs. 13,051). The former yields 45.57% of ARA in total fatty acids, while the latter 6.95%. The accumulation of ARA is speculated to be associated with delta-5 desaturase (Delta5) and elongation of very long chain fatty acids protein 3 (ELOVL3). A further genomic comparison of 19 strains in 10 species in three genera in the Mortierellaceae reveals three types of fatty acid synthase (FAS), two of which are new to science. The most common type I exists in 16 strains of eight species of three genera, and was discovered previously and consists of a single unit with eight active sites. The newly revealed type II exists only in M. antarctica KOD 1030 where the unit is separated into two subunits α and β comprised of three and five active sites, respectively. Another newly revealed type III exists in M. alpina AD071 and Dissophora globulifera REB-010B, similar to type II but different in having one more acyl carrier protein domain in the α subunit. This study provides novel insights into the enzymes related to the lipid metabolism, especially the ARA-related Delta5, ELOVL3, and FAS, laying a foundation for genetic engineering of Mortierellaceae to modulate yield in polyunsaturated fatty acids.